Peningkatan Kapasitas Forum Anak Tangsel Mengenai Pembangunan Kota dan Komunitas Berkelanjutan - Rizky Hikmawan; Rizkiya Ayu Maulida (Universitas Lancang Kuning, 2020)
The aim of the eleventh goal of Sustainable Development Goals (SDGs) is to create a livable city for its citizens. Therefore, this goal also intended to eliminate the problems faced by the city, such as: traffic, slum area, and the potential for natural or human made disaster. The Government of Tangsel must always prepare themselves to resolve all the problems to create a livable city. However, the responsibility for resolving existing problems does not only lie with the Government of Tangsel. The citizens are also demanded to be able to contribute to the sustainable development of the city and its communities. One of the communities in this city is Forum Anak Tangsel (Fatangsel). Therefore, we would like to facilitate a capacity building for Fatangsel to realizing their participation in developing their city and its communities through the perspective of SDGs.